A cross-cultural examination of the alchemical origins underlying medicinal uses of mercury across Eurasia - Bentley, Felix (My University, 2025)
This study aims to investigate the different cultural perspectives that underline historical uses of mercury in medicine across Eurasia in the pre-industrial period. In attempts to compare and contrast the differences and similarities between these medicinal uses of mercury, this project reviews literature exploring the developmental origins of medicine from several general regions, including China, the Mediterranean, India, the Arabic world, and Western Europe. This investigation shows that Eurasian medicinal uses of mercury are closely related to alchemical philosophy and deeply intertwined with spirituality. The results of this study also show that uses and perceptions of mercury were highly similar across the continent, having been viewed as an element imbued with supernatural and transformational power, and likely developed due to centuries of academic and cultural exchange between these five major centres of civilization.
Presented on April 17, 2025 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: mercury; medicine; cross-cultural; Eurasia